Mengukir Senyum Lewat Poster Senyum - Ahmad, Arif Priyono Susilo; Ariesta, Inda (Humaniora, 2011)
Poster is a communications media that are generally in a large enough format with persuasive and informative messages, pasted on the walls on the roadside and residential alleys. Posters can be so effective in conveying the message as a poster is close to the heart of society. The effectiveness of posters in conveying the message can be seen in the winning poster design of the Smiling Poster Contest 2010. The purpose of this article is to see the effectiveness of communication and poster design in a persuasive smile. A smiling poster is intended to foster and to remind the meaning of a smile in socializing. Concern of poster designers were divided into concern for social problems that occur in society and concern in the development of poster design creativity. Technical and strategic skills are needed by designers of the poster. Since poster design works well, it will eventually become a communicative medium in conveying social messages, becomes the driving motivation in positive, open, creative and inspiring thinking.